Research progress on the role of histone acetylation regulatory factors during the early embryonic development in animals - LI Xiaoteng; ZHAO Panpan; ZHANG Kun (浙江大学学报. 农业与生命科学版, 2024)
Following sperm-egg fusion, animal embryos undergo severe epigenetic reprogramming during the early development, encompassing DNA methylation, histone modification, as well as chromatin remodeling, to ensure that highly differentiated gametes form totipotent embryonic cells upon fertilization. Reprogramming is intimately connected to each stage of early embryonic development, and numerous regulatory factors are involved, such as acetyltransferases, deacetylases and histone modification readers, which participate in the regulation of histone acetylation and serve crucial functions. This review summarizes the roles of histone acetylation regulatory factors in the early embryonic development of animals, discusses epigenetic phenomena and mechanisms during the early embryonic development, contributes to a better understanding of the developmental mechanisms of mammalian early embryos, reduces embryonic developmental defects, and enhances livestock fertility.